The effect of physical exercise on blood glucose levels in patients with type 2 diabetes mellitus - Siregar, Annisa Surto; Ginting, Rapael; Putri, Nadya Nazimuddin; Leslie, William; Hutabarat, Bartimeus Nicomama; Syahputra, Ari Denggan (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by hyperglycemia. This study aimed to analyze the effect of physical exercise on blood glucose levels in patients with Type 2 DM at the Medan Johor Public Health Center. This analytical observational study utilized a case-control design and involved 34 respondents, divided into a case group (with uncontrolled blood glucose levels) and a control group (with controlled blood glucose levels). Data on physical activity, including frequency, duration, and intensity of exercise, were obtained through interviews using the GPAQ questionnaire, while blood glucose level data were sourced from medical records. The results showed a significant relationship between physical activity (p=0.028), frequency of physical exercise (p=0.006), duration of physical exercise (p=0.015), and intensity of physical exercise (p=0.034) with blood glucose levels. Physical exercise performed at least three times a week, for a minimum duration of 30 minutes per session, and at an appropriate intensity proved effective in controlling blood glucose levels in patients with Type 2 DM. This study emphasizes the importance of incorporating physical exercise into the management plan for Type 2 DM.